Feasibility of Social Media-Based Recruitment and Perceived Acceptability of Digital Health Interventions for Caregivers of Justice-Involved Youth: Mixed Methods Study - Folk, Johanna Bailey; Harrison, Anna; Rodriguez, Christopher; Wallace, Amanda; Tolou-Shams, Marina (JMIR Publications, 2020)
BackgroundCaregiver involvement is critical for supporting positive behavioral health and legal outcomes for justice-involved youth; however, recruiting this population into clinical research studies and engaging them in treatment remain challenging. Technology-based approaches are a promising, yet understudied avenue for recruiting and intervening with caregivers of justice-involved youth. ObjectiveThis mixed methods study aimed to assess the feasibility of recruiting caregivers of justice-involved youth using social media into clinical research and to understand caregivers' perceptions of the acceptability of digital health interventions. MethodsCaregivers of justice-involved youth were recruited through paid Facebook advertisements to participate in a Web-based survey. Advertisement design was determined using Facebook A/B split testing, and the advertisement with the lowest cost per link click was used for the primary advertisement campaign. Survey participants were offered the option to participate in a follow-up qualitative phone interview focused on the perceived feasibility and acceptability of digital health interventions. ResultsFacebook advertisements were successful in quickly recruiting a diverse set of caregivers (80/153, 52.3% female; mean age 43 years, SD 7; 76/168, 45.2% black, 34/168, 20.2% white, and 28/168, 16.7% Latinx; and 97/156, 62.2% biological parents); cost per click was US $0.53, and conversion rate was 11.5%. Survey participants used multiple social media platforms; 60.1% (101/168) of the participants indicated they would participate in a digital health intervention for caregivers of justice-involved youth. Survey respondents' most preferred intervention was supportive and motivational parenting messages via SMS text message. Of the survey respondents, 18 completed a phone interview (12/18, 67% female; mean age 45 years, SD 10; 10/18, 56% black, 7/18, 39% white, and 1/18, 6% Latinx; and 16/18, 89% biological parents). Interview participant responses suggested digital health interventions are acceptable, but they expressed both likes (eg, alleviates barriers to treatment access) and concerns (eg, privacy); their most preferred intervention was video-based family therapy. ConclusionsRecruiting and intervening with caregivers of justice-involved youth through social media and other digital health approaches may be a feasible and acceptable approach to overcoming barriers to accessing traditional in-person behavioral health care.